Cocoanut [sic] Palm, Trinidad - (:unkn) unknown (My University, 2009)
A picture looking out onto the ocean at two small islands through coconut trees on the shoreline. Affixed to the back of the postcard is a Trinidad and Tobago 2 cents stamp.
Colour: Black and White; Style: Portrait; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Coconut palm--Trinidad and Tobago; Agriculture--Trinidad and Tobago; Shorelines--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Mayaro